2023
DOI: 10.3748/wjg.v29.i2.286
|View full text |Cite
|
Sign up to set email alerts
|

Screening and interventions to prevent nonalcoholic fatty liver disease/nonalcoholic steatohepatitis-associated hepatocellular carcinoma

Abstract: Liver cancer is the sixth most commonly diagnosed cancer worldwide, with hepatocellular carcinoma (HCC) comprising most cases. Besides hepatitis B and C viral infections, heavy alcohol use, and nonalcoholic steatohepatitis (NASH)-associated advanced fibrosis/cirrhosis, several other risk factors for HCC have been identified ( i.e. old age, obesity, insulin resistance, type 2 diabetes). These might in fact partially explain the occurrence of HCC in non-cirrhotic patients without viral inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 237 publications
(294 reference statements)
0
17
0
Order By: Relevance
“…This was also demonstrated in the meta-analysis by Dulai et [4.11-9.95] from F1 to F4) [58]. In addition, the presence of advanced liver fibrosis modifies the clinical management, as it requires periodic surveillance for HCC, and in patients with T2DM it may influence the choices of antihyperglycemic therapeutic agents (mainly in advanced cirrhosis, when insulin might become the only option) [17,59].…”
Section: Factors Associated With Fibrosis Progression and Regressionmentioning
confidence: 76%
See 3 more Smart Citations
“…This was also demonstrated in the meta-analysis by Dulai et [4.11-9.95] from F1 to F4) [58]. In addition, the presence of advanced liver fibrosis modifies the clinical management, as it requires periodic surveillance for HCC, and in patients with T2DM it may influence the choices of antihyperglycemic therapeutic agents (mainly in advanced cirrhosis, when insulin might become the only option) [17,59].…”
Section: Factors Associated With Fibrosis Progression and Regressionmentioning
confidence: 76%
“…Similarly, the prevalence of advanced fibrosis (F2-4) was reported to be around 5-7% in the general population, and 12-20% in patients with T2DM [10][11][12][13][14][15][16]. Moreover, the risk of HCC is 2.0-2.5 fold higher in subjects with T2DM [17][18][19][20]. A recent individual participant-level data meta-analysis of six retrospective studies (2016 participants with NAFLD) indicated that T2DM was an independent predictor of incident HCC (adjusted hazard ratio (HR): 5.34 [1.67-17.09], p = 0.0048) and of incident hepatic decompensation (adjusted HR: 2.15 [1.39-3.34], p = 0.0006) [21].…”
Section: Nafld and T2dm Bidirectional Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 Alcohol dependence, smoking, old age, obesity, insulin resistance, and type 2 diabetes are also risk factors for HCC. 4 The invasive potential, metastasis, lower surgical resection rate, higher recurrence rate, and insensitivity to chemotherapy are fundamental causes of the higher mortality rate linked to HCC compared with other types of cancer. 5 The higher recurrence rate of HCC after surgery is the main reason affecting the long-term survival rate of patients.…”
Section: Introductionmentioning
confidence: 99%